Birdwatching - Uys, Mia (WritingThreeSixty: Journal or Research and Creative Text, 2021)
It is raining when William wakes up, and he spends the first moment of his day thinking about his mother, while watching Cape robin-chats hop around the wet grass trying to pull worms out from the soil. He has always liked birds. They seem so detached from the world, witnessing life from high above, tied to nothing. Deep down, he knows this is just an illusion, a romantic idea that creatures with wings are somehow free. He knows birds are constrained by the same physical limitations that affect all living things on earth. Like him, they are hopelessly attached to many things.